1989
DOI: 10.1136/jnnp.52.4.493
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of factors affecting progress of patients on a stroke unit.

Abstract: SUMMARY The aim of the study was to identify factors affecting the progress in physical abilities and activities of daily living of patients admitted to a stroke unit. A series of 70 patients admitted consecutively were assessed on a series of tests of motor, functional and cognitive abilities at admission. They were assessed for level ofmotor abilities and activities ofdaily living at discharge and 9 months after stroke. Predictive equations were developed which account for between 61% and 33 % of the varianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
36
2
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 9 publications
1
36
2
1
Order By: Relevance
“…For example, Lincoln et al 6 concluded that motor deficits had a larger impact than did perceptual deficits on the ADL. However, they admitted that their measure of motor capacities was much more refined than was their measure of perceptual deficits, which might explain why they did not find a strong relationship between perceptual …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Lincoln et al 6 concluded that motor deficits had a larger impact than did perceptual deficits on the ADL. However, they admitted that their measure of motor capacities was much more refined than was their measure of perceptual deficits, which might explain why they did not find a strong relationship between perceptual …”
Section: Discussionmentioning
confidence: 99%
“…4 -7 Studies by Sea et al 8 and by Bechinger and Tallis 9 also report a significant link between sensory deficits and performance of the ADL. Lincoln et al, 6 Carter et al, 10 and Tatemichi et al 11 reported a significant correlation between various components of the ADL and one or many particular cognitive components. Hajek et al 12 attributed 23% of the variance in performance on various functional evaluations to cognitive deficits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not surprising that these two measures paralleled each other because motor function is a particularly important determinant of physical function and independence in ADL after stroke in humans. 31 Yet analysis of our data 'Sample size required in each of two groups to detect a 50% further improvement (of remaining potential improvement) with 80% power, a=0.05, by the two-tailed test. reveals that patients may score a perfect 100 on the Barthel Index but continue to have the same level of motor impairment.…”
Section: Discussionmentioning
confidence: 99%
“…A major contributor to emotional distress in caregivers of stroke patients occurs when the patient has anosognosia (Knapp & Hewison, 1999), yet precious little is available to effectively manage such cognitive deficits. No wonder that cognitive disorders are consistently found to be a reliable predictor of poorer quality of life (Galski et al, 1993;Kalra et al, 1997) and of institutionalization (Lincoln et al, 1989) compared with those who have brain impairments but not cognitive deficits.…”
mentioning
confidence: 99%